2004
DOI: 10.1037/0021-9010.89.2.293
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Leadership Theories in Applied Settings: Factor Structure, Generalizability, and Stability Over Time.

Abstract: The present empirical investigation had a 3-fold purpose: (a) to cross-validate L. R. Offermann, J. K. Kennedy, and P. W. Wirtz's (1994) scale of Implicit Leadership Theories (ILTs) in several organizational settings and to further provide a shorter scale of ILTs in organizations; (b) to assess the generalizability of ILTs across different employee groups, and (c) to evaluate ILTs' change over time. Two independent samples were used for the scale validation (N1 = 500 and N2 = 439). A 6-factor structure (Sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
639
4
23

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 501 publications
(710 citation statements)
references
References 79 publications
19
639
4
23
Order By: Relevance
“…Such perceptions have been shown to influence evaluations of actual leadership quality (e.g. Epitropaki & Martin, 2004) and are likely to play a role in determining the allocation of rewards in organisations. A greater understanding of the basic factors that determine these perceptions, including facial features, is important in developing a more complete understanding of the processes involved in leadership perceptions in organisations.…”
Section: Facial Cues Managerial Roles and Leadership Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Such perceptions have been shown to influence evaluations of actual leadership quality (e.g. Epitropaki & Martin, 2004) and are likely to play a role in determining the allocation of rewards in organisations. A greater understanding of the basic factors that determine these perceptions, including facial features, is important in developing a more complete understanding of the processes involved in leadership perceptions in organisations.…”
Section: Facial Cues Managerial Roles and Leadership Theorymentioning
confidence: 99%
“…Implicit leadership theories traditionally propose that naïve individuals develop personal assumptions of what traits and abilities are ideal in leaders through socialisation and experience (Epitropaki & Martin, 2004). The implicit assumptions that lay individuals hold concerning leadership have been found to reflect eight leader attributes, namely sensitivity, dedication, tyranny, charisma, attractiveness, masculinity, intelligence, and strength (Offerman, Kennedy & Wirtz, 1994).…”
Section: Facial Cues Managerial Roles and Leadership Theorymentioning
confidence: 99%
“…First, narcissists embody many of the traits associated with a prototypical leader. Studies have shown that individuals hold implicit theories about the attributes of an effective leader (e.g., Epitropaki & Martin, 2004;Offermann, Kennedy, & Wirtz, 1994). These assumptions are used to evaluate whether a person fits the prototype of a leader, including dimensions such as strength, masculinity, charisma, and attractiveness.…”
Section: The Narcissistic Leadermentioning
confidence: 99%
“…Socio-cognitive approaches to leadership (e.g., Epitropaki & Martin, 2004;Epitropaki et al, 2013;Lord & Maher, 1991;Shondrick, Dinh & Lord, 2010; and creativity (e.g., Christensen, Drewsen & Maaløe, 2014;Hass, 2014;Sternberg, 1985) open up exciting possibilities for creative leadership and may help resolve the paradox indicated in our introduction: On the one hand, prior studies (e.g., highlighted the importance of creative thinking skills for creative leadership; on the other hand, studies of Implicit Leadership Theories (ILTs) and Implicit Followership Theories (IFTs) have revealed a striking absence of the trait "creative" from existing lists of ILTs and IFTs (e.g., Offermann et al, 1994;Sy, 2010). As a matter of fact, in Lord, Foti, and De Vader's (1984) list the trait 'creative' was included in the non-leader attributes list which clearly implies that creativity is not perceived as a core characteristic of leadership .…”
Section: Implications For Research On Leadership Schemas Social Idenmentioning
confidence: 99%
“…Despite the growing realization that creativity is a central ability for leaders in promoting change (Shalley & Gilson, 2004), there is a striking absence of the trait 'creative' from existing lists of Implicit Leadership Theories (e.g., Epitropaki & Martin, 2004;Epitropaki, Sy, Martin, Tram-Quon & Topakas, 2013;Offermann, Kennedy & Wirtz, 2004;, and creative individuals are less likely to emerge as leaders (Kark, Miron-Spektor, Kaplon & Gorsky, 2012;Mueller, Goncalo, & Kamdar, 2011). Most organizations tend to promote executives who preserve the status quo, do not take risks, and stick to useful and working solutions Mueller et al, 2011), although many organizations claim that creative leadership is essential to them.…”
Section: Introductionmentioning
confidence: 99%